Students’ Experiences of Left-Right Game in Writing Narrative Text: A Narrative Inquiry Study - Ikariya Sugesti; Ida Saadatul Wuzaro (ELLITE, 2022)
The present study is aimed at exploring students’ experiences of using left-right game in writing narrative text. Narrative inquiry is used to capture students’ experiences of left-right games told in their narrative frames. This study concerned one class at the tenth grade purposively determined senior high school students in Indonesian context which consist of thirty-one students. Student’s narrative frame, semi structured interview and observation are the instruments employed to collect data. Their narratives reflect positive experiences in using left right games as a strategy to help them in writing narrative text. The findings of this study show that 87 % of the students state positive experiences in using left-right game activity in writing narrative text. They state that left-right game is a fun activity, they feel enthusiast when the teacher conduct left-right game. The students who engage through left-right game activity can find the way to equally and mutually collaborate in producing better a piece of writing.